The Effect of Structured Jigsaw Technique and Unstructured Group Work on The Listening Achievement of Junior High School Students - Agustin Santoso (Magister Scientiae, 2008)
Nowadays, English has been used as the most important foreign language in Indonesia. Many schools have used it as their important subject to be taught to the students. The English teaching can cover 4 language skills: listening, speaking, reading, and writing, all of them are important, especially listening. Listening is not an easy subject to master. It needs the teacher’s role in teaching that skill. In this study, the writer would like to know whether there is a significant difference between the listening achievement of learners taught by using structured jigsaw technique and unstructured group work technique, especially in answering the three types of questions. The writer took the data from St. Clara Junior High School and the population is the second grade students. The writer took VIIIB as the control group and VIIIC as the experimental group. The writer administered pretest before the treatment to see the level of the students’ listening ability. After that, she conducted three times treatment by using structured jigsaw technique in the experimental group and unstructured group work in the control group. The posttest was administered and then the writer analyzed the mean scores by using t-test. From the analysis of the pretest, the writer found out that those two groups had equal ability in listening achievement. From the posttest scores, the writer also found out that those two groups were not significantly different. It means that the null hypothesis which says “There is no significant difference in listening achievement between the second grade Junior High School students who are taught using jigsaw technique and those who are taught using unstructured group work” was accepted. Further analysis found that jigsaw technique could improve the students’ listening ability in answering main idea questions.